2019
DOI: 10.1016/j.gca.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Tracing silicate weathering processes in the permafrost-dominated Lena River watershed using lithium isotopes

Abstract: Tracing silicate weathering processes in the permafrost-dominated Lena River watershed using lithium isotopes. Geochimica et Cosmochimica Acta 245 , pp. 154-171.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 80 publications
1
32
1
Order By: Relevance
“…Mg/Na ratios should therefore provide information on dissolution of primary minerals vs. formation and uptake by secondary minerals. However, unlike the isotope ratios of trace elements such as lithium Murphy et al, 2019), we do not observe a simple relationship between δ 26 Mg and Mg/Na or Ca/Mg for either coast, which is not necessarily to be expected, given the variable isotope ratios of both silicates and carbonates. Similarly, there is no relationship between δ 26 Mg and the ratio of divalent to monovalent cations, which has also been used as a proxy for silicate weathering (Tranter et al, 2002;Hatton et al, 2019).…”
Section: Riverine Magnesiumcontrasting
confidence: 92%
See 1 more Smart Citation
“…Mg/Na ratios should therefore provide information on dissolution of primary minerals vs. formation and uptake by secondary minerals. However, unlike the isotope ratios of trace elements such as lithium Murphy et al, 2019), we do not observe a simple relationship between δ 26 Mg and Mg/Na or Ca/Mg for either coast, which is not necessarily to be expected, given the variable isotope ratios of both silicates and carbonates. Similarly, there is no relationship between δ 26 Mg and the ratio of divalent to monovalent cations, which has also been used as a proxy for silicate weathering (Tranter et al, 2002;Hatton et al, 2019).…”
Section: Riverine Magnesiumcontrasting
confidence: 92%
“…In other words, the enhanced dissolution of primary silicates in mountainous regions causes a correlation of Li and Si isotopes (also observed in the Himalayan foothills; Pogge von Strandmann et al, 2017). This co-relationship between the two systems can be modeled using a Rayleigh relationship (Vigier et al, 2009;Pogge von Strandmann et al, 2012, 2014b, 2017Murphy et al, 2019), and by assuming a continental crust starting composition (Savage et al, 2010;Sauzéat et al, 2015). Using a kaolinite fractionation factor of α = 0.979 for Li isotopes (Pistiner and Henderson, 2003;Hindshaw et al, 2019), and of 0.9989 for Si isotopes (close to values for allophane, which is compositionally similar to kaolinite; Ziegler et al, 2005;Delstanche et al, 2009), we can model the co-isotopic behavior for the western samples with between 20 and 60% of Li and Si removal (Figure 4E).…”
Section: Riverine Siliconmentioning
confidence: 99%
“…Thus, while there are apparently subtle differences in fractionation between different terrains (bearing in mind that riverine suspended loads do not necessarily only consist of secondary minerals), observed fractionations appears to be broadly similar, around ~20‰. The observed fractionation in these experiments is also similar to the overall variability observed in a global compilation of published riverine values (Murphy et al, 2019), and the mean discharge-weighted d 7 Li of ~23‰ observed in rivers (Huh et al, 1998).…”
Section: Mineral Saturation Statessupporting
confidence: 70%
“…Instead, the light Li isotope ( 6 Li) is preferentially taken up by secondary minerals (clays, oxides, zeolites) formed during weathering, enriching residual waters in isotopically heavy Li. Hence, surface water δ 7 Li is controlled by the ratio of primary rock dissolution to secondary mineral formation, known as the weathering congruency (Misra and Froelich, 2012;Pogge von Strandmann and Henderson, 2015), which in turn can act as a tracer of weathering intensity (that is, the ratio of the weathering rate to the denudation rate, Dellinger et al, 2015;Pogge von Strandmann et al, 2017;Murphy et al, 2019;Gou et al, 2019). This also relates to the efficiency of CO 2 drawdown, as cations retained on the continents in secondary minerals do not end up in the oceans to assist carbon sequestration (Pogge von Strandmann and Henderson, 2015;Pogge von Strandmann et al, 2017).…”
Section: Application Of Sr Os LI and Ca Isotopes As Proxies Of Weatmentioning
confidence: 99%